(untitled) (Third Sector Social Economic Review, 2025)
The human development index is calculated as a broad index that includes national income per capita as a proxy for income as well as human and social components such as education and health. The human development index, which is frequently used in studies on income inequality, is known to have a strong relationship with income distribution. This study aims to measure the relationship between human development and income distribution through the Turkish sample. For this purpose, the annual data of the gini index, which is an indicator of income inequality, and the human development index (HDI) between 1990 and 2020 are used. The existence of a long-run relationship between the variables was measured using the ARDL bounds test approach. According to the findings of the study, a 1% increase in the human development index decreases the Gini index by 0.138%. In other words, increases in human development reduce income inequality. It is concluded that a 1% increase in the inflation rate (lnINF), which is included in the model as a control variable, increases income inequality by 0.120%. When these results are analyzed, it is seen that improving the sub-components of the human development index, i.e. increasing the income of individuals in real terms, providing easy access to and sustaining education opportunities and improving the opportunity to benefit from health services in all aspects, is an important tool in reducing income inequality. At this point, policy makers should implement policies based on the income variable in the short run and the education and health variables in the long run, taking into account the instruments with high impact power while producing economic policies such as economic growth and development plans